Child Maltreatment, Early Adult Substance Use, and Mediation by Adolescent Behavior Problems. (May 2021) - Dubowitz, Howard; Roesch, Scott; Lewis, Terri
The purpose of the current study was to examine the potential mediating effects of internalizing and externalizing problems at ages 14, 16 and 18 between types of childhood maltreatment and alcohol and marijuana use problems and disorders in young adulthood. Data were from 473 young adults who participated in the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). Path analysis was conducted to examine pathways between maltreatment type (birth through age 12), internalizing and externalizing problems at three time points during adolescence, and alcohol and marijuana problem use in young adulthood. Findings indicated significant pathways between physical abuse and internalizing problems at 14, which was associated with alcohol-related substance use disorder in adulthood. Externalizing problems and internalizing problems at age 14 mediated the relationship between physical abuse and marijuana-related symptoms in young adulthood. Emotional and sexual abuse were not associated with substance use problems. Implications for practice are discussed.